Motivasi Kerja Aparatur Bidang Ketentraman Dan Ketertiban Umum Di Dinas Satuan Polisi Pamong Praja Dan Pemadam Kebakaran Kabupaten Pasangkayu - Tinggogoy, Filo Leonardo; Rapi, Muh (Jurnal ADMINISTRATOR, 2022)
The aim of this research is to determine work motivation in the firefighting field at the civil service police and fire service in Pasangkayu Regency. The informants in this research were officials from the Civil Service Police and Fire Department office. Apart from that, to determine work motivation, this research data consists of primary data and secondary data obtained directly through field research (interviews). The data was analyzed using the results of interviews with the Southern Civil Service and Fire Police Unit Service Head, Service Secretary, General and Personnel Sub-Section, Fire Fighting and Staff Section. The results of the research show that to determine the work motivation of officials in administering government at the Civil Service Police and Fire Service offices. The author chose a theory that is considered more suitable to be applied to government organizations, in this case the Padangkayu Regency Civil Service Police and Fire Service, if implemented simultaneously, good service quality will be realized, namely David McClelland's theory in Mangkunegara (2001: 97 - 98), namely: Need for Achievement, Need for Power, and Need for Affiliation. What was highlighted by the informants from the interview results was that work motivation which was considered not optimal in its implementation was the need for achievement and the need for power, while the indicators/dimensions of need for affiliation whose results were still not being implemented well. The influencing factors are the capability of human resources which is an important aspect of the smooth running of public services in the organization